Hasil Belajar Siswa Kelas X Materi Kuda-Kuda Atap Menggunakan E-Book Interaktif di SMKN 2 Surabaya - gunawan saputra; Suparji Suparji (Jurnal Kajian Pendidikan Teknik Bangunan, 2023)
Student learning outcomes using conventional teaching modules only get an average of 80, and there are some students who still have scores below the average. Based on observations of the score data, it is necessary to provide teaching materials that support and can attract students to be more active in their learning. This research aims (1) to determine learning outcomes using printed modules, (2) to determine learning outcomes using E-Books, (3) to determine differences in learning outcomes between using printed module teaching materials and Interactive E-Books. The research method used is a quantitative experimental method of the Quasi Experimental Design type with a design of the Non Equivalent Group Design type. The sample used was 65 students using purposive sampling technique. Data collection techniques use tests (pre-test and post-test), questionnaires, and interviews. The results of the data that have been obtained are then processed using the chi-square test for hypotheses 1 and 2, while the Mann-Whitney test for hypothesis 3. The results of the analysis show that, 1) hypothesis 1 uses chi square with Chi2h = 46.08 > Chi2t = 7 .8, meaning H0 is rejected and H1 is accepted. The learning results using the printed module are above 81. 2) hypothesis 2 uses chi square with Chi2h = 16.63 > Chi2t = 9.48, meaning that H0 is rejected and H1 is accepted. Learning results using Interactive E-Books are above 81. 3) hypothesis 3 uses the Mann-Whitney test with pvalue = 0.0467 < the significance level (5%), meaning that H0 is rejected and H1 is accepted. There are differences in student learning outcomes using printed modules and e-books. Keywords: Interactive E-Book, Learning Results, Easel and Roof.